Bioengineering strategies for restoring vision - Cehajic-Kapetanovic, Jasmina; Singh, Mandeep S.; Zrenner, Eberhart; MacLaren, Robert E. (Nature biomedical engineering, 2023)
Late-stage retinal degenerative disease involving photoreceptor loss can be treated by optogenetic therapy, cell transplantation and retinal prostheses. These approaches aim to restore light sensitivity to the retina as well as visual perception by integrating neuronal responses for transmission to the cortex. In age-related macular degeneration, some cell-based therapies also aim to restore photoreceptor-supporting tissue to prevent complete photoreceptor loss. In the earlier stages of degeneration, gene-replacement therapy could attenuate retinal-disease progression and reverse loss of function. And gene-editing strategies aim to correct the underlying genetic defects. In this Review, we highlight the most promising gene therapies, cell therapies and retinal prostheses for the treatment of retinal disease, discuss the benefits and drawbacks of each treatment strategy and the factors influencing whether functional tissue is reconstructed and repaired or replaced with an electronic device, and summarize upcoming technologies for enhancing the restoration of vision. This Review discusses the most promising gene therapies, cell therapies and retinal prostheses for the treatment of retinal degeneration, as well as upcoming technologies for enhancing vision restoration.